Advancing Health Professions Education Research by Creating a Network of Networks. (August 2018) - Carney, Patricia A.; Brandt, Barbara; Dekhtyar, Michael; Holmboe, Eric S.
Abstract : Producing the best evidence to show educational outcomes, such as competency achievement and credentialing effectiveness, across the health professions education continuum will require large multisite research projects and longitudinal studies. Current limitations that must be overcome to reach this goal include the prevalence of single-institution study designs, assessments of a single curricular component, and cross-sectional study designs that provide only a snapshot in time of a program or initiative rather than a longitudinal perspective. One solution to overcoming these limitations is to develop a network of networks that collaborates, using longitudinal approaches, across health professions and regions of the United States. Currently, individual networks are advancing educational innovation toward understanding the effectiveness of educational and credentialing programs. Examples of such networks include (1) the American Medical Association's Accelerating Change in Medical Education initiative, (2) the National Center for Interprofessional Practice and Education, and (3) the Accreditation Council for Graduate Medical Education's Accreditation System. In this Invited Commentary, the authors briefly profile these existing networks, identify their progress and the challenges they have encountered, and propose a vigorous way forward toward creating a national network of networks designed to determine the effectiveness of health professions education and credentialing.